Extent and determinants of left ventricular reverse remodeling in patients with secondary mitral regurgitation undergoing MitraClip implantation. (June 2021) - Spieker, Maximilian; Marpert, Jonathan; Afzal, Shazia; Scheiber, Daniel; Bönner, Florian; Horn, Patrick; Kelm, Malte; Westenfeld, Ralf
Abstract: Background: In secondary MR, data on left ventricular (LV) remodeling after MitraClip procedure are rare, even this information may impact patient selection. This study investigated changes in LV structure and function by cardiovascular magnetic resonance (CMR) following MitraClip implantation for secondary mitral regurgitation (MR) in order to assess extent and predictors of LV reverse remodeling (LVRR). Methods and Results: Twenty-nine patients underwent CMR imaging prior to and six months after MitraClip procedure. LVRR was defined by a decrease of LV end-diastolic volume index (LVEDVi) > 15% compared to baseline. According to the definition of LVRR, 34% of patients displayed LVRR at follow-up CMR. Baseline LV stroke volume index (LVSVi), LV ejection fraction (LVEF), LV circumferential strain and MR volume at baseline were predictors of LVRR at follow-up. At second CMR, we detected an improvement in hemodynamic status as illustrated by an increase in effective LVSVi (28 ± 8 ml/m 2 vs. 33 ± 8 ml/m 2 ; p = 0.053) and cardiac index (2.0 ± 0.5 vs. 2.3 ± 0.5 l/min; p = 0.016), while LVEF and LV strain parameters did not change (p > 0.05). Improvements in effective LVSVi were associated with the decrease of MR volume (r = 0.509; p = 0.018) and MR fraction (r = 0.629; p = 0.002) by MitraClip. Conclusions: Together, MitraClip implantation is associated with LVRR in one third of patients. Baseline LV function and magnitude of MR are important predictors of LVRR. Improvement of hemodynamic status may be assessed by effective stroke volume index and correlates with the reduction of MR by MitraClip implantation, rather than an increase in LV contractility.